Antibodies to intermediate filaments in polymyalgia rheumatica and giant cell arteritis: a sequential study. Issue 10 (October 1987) - Dasgupta, B; Duke, O; Kyle, V; Macfarlane, D G; Hazleman, B L; Panayi, G S
Abstract : Serum specimens from 35 patients with polymyalgia rheumatica and giant cell arteritis (PMR/GCA) were obtained sequentially at variable time intervals up to a year from onset of disease. These were tested for antibodies to intermediate filaments by indirect immunofluorescence using HEp2 cells as substrate. Twenty four of 35 (68%) patients' sera at onset of disease were positive at an anti-intermediate filament antibody (AIFA) titre of greater than 1/40 compared with three outs of 19 (15%) control sera. AIFA were predominantly of IgM class, and there was no significant change in AIFA titres on follow up despite clinical remission of disease.